Impact of freezing, on some basic components of marine fish flesh (Rabbit fish) caught from the Syrian marine water. (Latakia University Journal -Biological Sciences Series, 2013)
This work was designed to investigate the effect of temperature of frozen storage and its duration on some chemical properties (Protein, Ash, Moisture,Lipid) of fishes Rabbit fish (Siganus rivulatus). The fishes were subjected (from one weak to 150 day) of frozen storage at two  different degrees of low temperatures (-18 C,-24 C).Chemical analysis were done  including  evaluation of  (Protein, Ash, Moisture, Fat), for study type and the two freezing degree during the following freezing periods/7, 15, 30, 45, 60, 90, 120, 150 day/.The study was carried out  between  September  2011 and  May  2012 in Technical  Engineering Faculty  in Tartus , Tishreen University.Protein gradually decreases with increasing duration of frozen storage,compared with the fresh samples which recorded (20.6%) ,while (17.03, 17.99%) were recorded for fish samples that were frozen for (150) day at(-24, -18 C).On  the  other  hand, The  study showed no change  in percentage  proportions  of  ash during freezing duration for samples our study type and at the two freezing degrees  /-24, -18 C/,compared with the fresh samples.The study showed a decrease of  the percentage  of  moisture  in  the  first  periods of  storage  and  then  arise in  recent  periods of  freezing.The study showed a clear decrease  with  the  percentage  of  fat  from  the  first  week freezing  until  the  end of  the  freezing duration,for samples our study type and at the two freezing degrees /-24,   -18 C/,while  the  percentage  of  fat  which  frozen  for /7, 150/  day respectively at /-24 C/was  /7.12, 3.3%/, and at /-18 C/ was/ 7.12, 3.36%/.Note that  this  apparent  decrease  of  fat  percentage  was  faster  when  freezing  at /-18 C/ compared  with  freezing at /-24 C/.